(untitled) (Linguist, 2021)
This research assumes that de Saussure is not structuralist and that his work falls within the scope of establishing general linguistics addressing the linguistic phenomenon with the required methodical and conceptual dimensions. The study is based on a set of factors related to his research program and the intellectual foundations inspiring it. The study also draws on the arguments derived from the structure of his entire work, the understanding of the binary system, its operation and use in the Saussurean discourse, along with the complex language of the system that varies between order and disorder. The study also takes account of the nature of the intellectual climate and its characteristics, as well as the competing interpretations and readings due to intellectual and ideological backgrounds. The study is guided by a comprehensive and critical analytical approach, conducive to confirming the position that de Saussure was behind establishing all the schools of linguistics, and that the tendency to call him the father of structuralism - because of the priority granted to langue at the expense of parole - is due to the desire to upgrade scientific research through adopting appropriate methodologies. The epistemological dichotomy of langue and parole put forth by de Saussure is a non-differential move. It is rather systematic work that establishes a scientific practice which addresses the facts of both langue and parole and envisages the leveling, stability and consolidation of the linguistic system. This is because it is the aspect that has not received the required focus and comprehensive analysis.